Evaluasi Implementasi Pengungkapan Informasi Corporate Social Responsibility (CSR) pada PT Lambang Jaya dan PT Tunas Baru Lampung, Tbk - Eksa Ridwansyah; Damayanti Damayanti; Lihan Rini Puspo Wijaya (Politeknik Negeri Lampung, 2015)
This study aimed to quantify and analyze the level of disclosure of CSR activities as well as calculate and analyze the percentage of disclosures based on each theme disclosure of CSR activities. The methods used to answer the purpose are descriptive qualitative and descriptive quantitative. The data were collected through questionnaires and analyzed through content analysis on the disclosure of CSR in the company's annual report. The content analysis was conducted using the check list of the items of CSR disclosure in the annual report of the company. The items of the disclosure were classified by themes of the disclosure (Environment, Energy, Health and Safety of the Employment, miscellaneous of Labor, Products, Community and Public Involvement). It is known that the percentage of the disclosure was by the themes. Further, the results of quantitative descriptive analysis checklist are to determine the index of CSR. The results of the study are as follows: The disclosure level of CSR of PT PT Tunas Baru Lampung Tbk as a whole is equal to 46% which is lower than that of PT Lambang Jaya - 71.6%. Based on the themes of disclosure, the implementation of CSR is the best done by PT Lambang Jaya in the category of energy, health and safety, and general products with a percentage of 100%, and then successively followed by the environmental category of 90.9%, category